A composite solid electrolyte coating diaphragm and preparation method thereof

Through the use of composite solid -state electrolyte coating diaphragm in the semi -solid battery, the problem that existing diaphragm cannot meet multiple performance requirements at the same time, and realizes the effect of decreased resistance in the battery interface, improvement of ionic conductivity, and lithium branched crystal suppression. , Improve the safety and cycle stability of the battery.

CN115528382BActive Publication Date: 2025-01-28JIANGSU HORIZON NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211286063.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-20
Publication Date
2025-01-28
Estimated Expiration
2042-10-20

AI Technical Summary

Technical Problem

The existing semi-solid battery separators cannot meet the requirements of electrolytes with good wetting properties, stable interface, excellent shrinkage performance, high modulus, and high conductivity, resulting in high internal interface resistance, low ionic conductivity, and lithium dendrites. .

Method used

The preparation method of composite solid -state electrolyte coating diaphragm is used to add lithium salt, inorganic solid -state electrolyte and PVDF solution to the mixture of carbonate molecurantte and carbonate. Dividation of quantity and high ionic conductivity.

Benefits of technology

Reduce the interface resistance inside the battery, improve the ionic conductivity, promote the uniform deposition of lithium metal, suppress the production of lithium branches, and improve the high elastic modulus of materials, enhance the safety performance and cycle stability of the battery Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GHA0000007712870000061
    Figure GHA0000007712870000061
  • Figure GHA0000007712870000071
    Figure GHA0000007712870000071
Patent Text Reader

Abstract

The invention discloses a composite solid electrolyte coating diaphragm and a preparation method thereof. The preparation method of the diaphragm is to add 10-40wt% of lithium salt to a mixed solution of ethyl methyl carbonate and diethyl carbonate in a ratio of 1:4, then add 0.2-0.6wt% of initiator and 3-10wt% of inorganic solid electrolyte and NMP solution dissolved with 4wt% PVDF, and evenly coat the composite solid electrolyte coating liquid on a polypropylene base film by scraping, heat and cure, and then wash to obtain a composite solid electrolyte coating diaphragm. The composite solid electrolyte coating obtained by the invention is uniform, and the diaphragm prepared by the composite solid electrolyte coating can be used in CR2032 button batteries, greatly reducing the interface resistance inside the battery, improving the ionic conductivity, inducing the uniform deposition of lithium metal, improving the elastic modulus of the material itself, avoiding the penetration of lithium dendrites, and being able to meet the use of semi-solid batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of lithium ion battery diaphragm materials, and in particular to a composite solid electrolyte coating diaphragm and a preparation method thereof. Background Art

[0002] Solid-state lithium metal batteries have become the focus of current lithium secondary battery development due to their high energy density and good safety, and have received widespread attention. However, there are still many problems in the large-scale application of solid electrolytes: including unstable solid electrolyte interface, poor cycle performance, lithium dendrite growth, etc., which hinder their application in automobiles and power grids. Therefore, before solid-state lithium metal batteries completely replace liquid lithium-ion batteries, they can be transitioned through semi-solid-state batteries, that is, increasing the use of solid electrolytes, reducing the use of liquid electrolytes, and gradually developing towards all-solid-state batteries.

[0003] Semi-solid-state battery separators need to have good electrolyte wettability, stable interface, excellent thermal shrinkage performance, high modulus (≥6GPa) (Bingbin, Wang, Shanyu, et al. The role of the solid electrolyte interphase layer in preventing Li dendrite growth in solid-state batteries [J]. Energy & environmental science: EES, 2018, 11 (7): 1803-1810), high ionic conductivity, etc. However, neither commercial polyolefin separators nor solid electrolytes can meet the above requirements at the same time.

[0004] Therefore, designing a separator that can meet the needs of semi-solid-state batteries becomes a very critical technology. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the diaphragm in the current semi-solid battery cannot simultaneously meet the problems of good electrolyte wettability, interface stability, excellent shrinkage performance, high modulus, and high conductivity. A composite solid electrolyte coating diaphragm and a preparation method thereof are provided, which can greatly reduce the interface resistance inside the battery, improve ion conductivity, induce uniform deposition of lithium metal and the high elastic modulus of the material itself, avoid the penetration of lithium dendrites, and can meet the needs of semi-solid batteries.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0007] The preparation method of the composite solid electrolyte coating diaphragm of the present invention is to add lithium salt to a mixture of ethyl methyl carbonate and diethyl carbonate, then add an initiator and an inorganic solid electrolyte and an NMP solution containing 4wt% PVDF, and evenly coat the composite solid electrolyte coating liquid on a polypropylene base film by a doctor blade, heat and cure, and then wash with water to obtain a composite solid electrolyte coating diaphragm. The diaphragm is specifically prepared according to the following steps:

[0008] (1) Preparation of composite solid electrolyte coating solution:

[0009] First, ethyl methyl carbonate and diethyl carbonate are mixed and stirred in a weight ratio of 1:4 to form a uniform solution, then 10-40 wt% of lithium salt is added to the mixed solution of ethyl methyl carbonate and diethyl carbonate, then 0.2-0.6 wt% of initiator and 3-10 wt% of inorganic solid electrolyte are added thereto, and finally NMP solution containing 4 wt% PVDF is added to obtain a composite solid electrolyte coating solution;

[0010] (2) Preparation of composite solid electrolyte coated diaphragm:

[0011] The composite solid electrolyte coating liquid was evenly coated on the polypropylene base film by scraping on a glass plate with the polypropylene base film, and then heated in an oven at 80°C for 48 hours to completely polymerize and solidify the electrolyte. The composite solid electrolyte coating membrane was then obtained by washing with water twice to remove the residual NMP solvent.

[0012] As a limitation of the present invention, the lithium salt described in step (1) is lithium bis(difluoromethanesulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium difluorooxalatoborate, lithium fluoride, lithium perchlorate or lithium tetrafluoroborate.

[0013] As a limitation of the present invention, the initiator in step (1) is 2,2'-diazoisobutyronitrile, azobisisoheptanenitrile, diisopropylbenzene peroxide, cyclohexanone peroxide or dimethyl azobisisobutyrate.

[0014] As a limitation of the present invention, the inorganic solid electrolyte in step (1) is Li 10 GeP2S 12 , Li 1 / 2 La 1 / 2TiO3, Li2S-P2S5-Li4SiO4, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li 14 ZnGe4O 16 .

[0015] As a limitation of the present invention, the particle size D50 of the inorganic solid electrolyte is in the range of 0.4 to 1.5 microns.

[0016] The composite solid electrolyte coated diaphragm is used in CR2032 button batteries. The specific application conditions are: in an argon environment, the composite solid electrolyte coated diaphragm is placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium ion battery electrolyte is added to assemble the CR2032 button battery.

[0017] After adopting the above technical solution, the beneficial effects achieved by the present invention are:

[0018] (1) Through the heating polymerization of the polymer, the pores between the inorganic solid electrolytes are filled and the agglomeration of the inorganic solid electrolytes is suppressed, thereby achieving the uniformity of the composite solid electrolyte coating.

[0019] (2) The composite solid electrolyte coating exhibits a depolarizing effect at the interface between lithium metal and electrolyte, thereby avoiding uneven lithium deposition and further reducing the formation of lithium dendrites, providing the first barrier for semi-solid-state batteries.

[0020] (3) Studies have shown that high modulus electrolytes have a physical shielding effect on lithium dendrites. Dense inorganic solid electrolytes have just such characteristics, thus inhibiting the penetration of lithium dendrites and providing a second safety barrier for the safety of semi-solid batteries.

[0021] (4) Through the composite of polymer electrolyte and inorganic electrolyte, not only the interface stability between polymer electrolyte and electrode is maintained and the interface resistance is reduced, but also the introduction of inorganic electrolyte greatly improves the ionic conductivity of solid electrolyte coating. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with specific implementation modes, but the protection scope of the following embodiments is not limited thereto.

[0023] Example 1

[0024] (1) Preparation of composite solid electrolyte coating solution:

[0025] First, ethyl methyl carbonate and diethyl carbonate were mixed and stirred in a weight ratio of 1:4 to form a uniform solution, and then 20 wt% of lithium bis(difluoromethanesulfonyl)imide was added to the mixture of ethyl methyl carbonate and diethyl carbonate, and then 0.3 wt% of 2,2'-diazoisobutyronitrile and 5 wt% of Li 10 GeP2S 12 The inorganic solid electrolyte is finally added with a NMP solution containing 4 wt% PVDF to obtain a composite solid electrolyte coating solution.

[0026] (2) Preparation of composite solid electrolyte coated diaphragm:

[0027] On a glass plate with a polypropylene base film laid flat, the composite solid electrolyte coating liquid is evenly coated on the polypropylene base film by scraping, and then heated in an oven at 80°C for 48 hours to allow the electrolyte to completely polymerize and solidify, and then washed with water twice to remove the residual NMP solvent, thereby obtaining a composite solid electrolyte coated diaphragm.

[0028] (3) Assembly of button batteries:

[0029] In an argon environment, the composite solid electrolyte coated diaphragm was placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium-ion battery electrolyte was added to assemble a CR2032 button battery.

[0030] Example 2

[0031] (1) Preparation of composite solid electrolyte coating solution:

[0032] First, ethyl methyl carbonate and diethyl carbonate were mixed and stirred in a weight ratio of 1:4 to form a uniform solution, and then 30 wt% of lithium bis(difluoromethanesulfonyl)imide was added to the mixture of ethyl methyl carbonate and diethyl carbonate, and then 0.3 wt% of 2,2'-diazoisobutyronitrile and 5 wt% of Li 10 GeP2S 12 The inorganic solid electrolyte is finally added with a NMP solution containing 4 wt% PVDF to obtain a composite solid electrolyte coating solution.

[0033] (2) Preparation of composite solid electrolyte coated diaphragm:

[0034] On a glass plate with a polypropylene base film laid flat, the composite solid electrolyte coating liquid is evenly coated on the polypropylene base film by scraping, and then heated in an oven at 80°C for 48 hours to allow the electrolyte to completely polymerize and solidify, and then washed with water twice to remove the residual NMP solvent, thereby obtaining a composite solid electrolyte coated diaphragm.

[0035] (3) Assembly of button batteries:

[0036] In an argon environment, the composite solid electrolyte coated diaphragm was placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium-ion battery electrolyte was added to assemble a CR2032 button battery.

[0037] Example 3

[0038] (1) Preparation of composite solid electrolyte coating solution:

[0039] First, ethyl methyl carbonate and diethyl carbonate were mixed and stirred in a weight ratio of 1:4 to form a uniform solution, and then 20 wt% of lithium perchlorate was added to the mixture of ethyl methyl carbonate and diethyl carbonate, and then 0.3 wt% of 2,2'-diazoisobutyronitrile and 8 wt% of Li 10 GeP2S 12 The inorganic solid electrolyte is finally added with a NMP solution containing 4 wt% PVDF to obtain a composite solid electrolyte coating solution.

[0040] (2) Preparation of composite solid electrolyte coated diaphragm:

[0041] On a glass plate with a polypropylene base film laid flat, the composite solid electrolyte coating liquid is evenly coated on the polypropylene base film by scraping, and then heated in an oven at 80°C for 48 hours to allow the electrolyte to completely polymerize and solidify, and then washed with water twice to remove the residual NMP solvent, thereby obtaining a composite solid electrolyte coated diaphragm.

[0042] (3) Assembly of button batteries:

[0043] In an argon environment, the composite solid electrolyte coated diaphragm was placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium-ion battery electrolyte was added to assemble a CR2032 button battery.

[0044] Example 4

[0045] (1) Preparation of composite solid electrolyte coating solution:

[0046] First, ethyl methyl carbonate and diethyl carbonate were mixed and stirred in a weight ratio of 1:4 to form a uniform solution, and then 10 wt% of lithium bis(trifluoromethanesulfonylimide) was added to the mixture of ethyl methyl carbonate and diethyl carbonate, and then 0.6 wt% of azobis(isoheptyl)carbonitrile and 3 wt% of Li 14 ZnGe4O 16 The inorganic solid electrolyte is finally added with a NMP solution containing 4 wt% PVDF to obtain a composite solid electrolyte coating solution.

[0047] (2) Preparation of composite solid electrolyte coated diaphragm:

[0048] On a glass plate with a polypropylene base film laid flat, the composite solid electrolyte coating liquid is evenly coated on the polypropylene base film by scraping, and then heated in an oven at 80°C for 48 hours to allow the electrolyte to completely polymerize and solidify, and then washed with water twice to remove the residual NMP solvent, thereby obtaining a composite solid electrolyte coated diaphragm.

[0049] (3) Assembly of button batteries:

[0050] In an argon environment, the composite solid electrolyte coated diaphragm was placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium-ion battery electrolyte was added to assemble a CR2032 button battery.

[0051] Example 5

[0052] (1) Preparation of composite solid electrolyte coating solution:

[0053] First, ethyl methyl carbonate and diethyl carbonate were mixed and stirred in a weight ratio of 1:4 to form a uniform solution, and then 40 wt% of lithium difluorooxalatoborate was added to the mixture of ethyl methyl carbonate and diethyl carbonate, and then 0.2 wt% of diisopropylbenzene peroxide and 10 wt% of Li 1 / 2 La 1 / 2 TiO3 inorganic solid electrolyte, and finally adding NMP solution dissolved with 4wt% PVDF to obtain a composite solid electrolyte coating liquid.

[0054] (2) Preparation of composite solid electrolyte coated diaphragm:

[0055] On a glass plate with a polypropylene base film laid flat, the composite solid electrolyte coating liquid is evenly coated on the polypropylene base film by scraping, and then heated in an oven at 80°C for 48 hours to allow the electrolyte to completely polymerize and solidify, and then washed with water twice to remove the residual NMP solvent, thereby obtaining a composite solid electrolyte coated diaphragm.

[0056] (3) Assembly of button batteries:

[0057] In an argon environment, the composite solid electrolyte coated diaphragm was placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium-ion battery electrolyte was added to assemble a CR2032 button battery.

[0058] Example 6

[0059] (1) Preparation of composite solid electrolyte coating solution:

[0060] First, ethyl methyl carbonate and diethyl carbonate were mixed and stirred in a weight ratio of 1:4 to form a uniform solution, and then 30 wt% of lithium tetrafluoroborate was added to the mixture of ethyl methyl carbonate and diethyl carbonate, and then 0.5 wt% of dimethyl azobisisobutyrate and 6 wt% of Li 1.3 Al 0.3 Ti 1.7 (PO4)3 inorganic solid electrolyte, and finally adding NMP solution dissolved with 4wt% PVDF to obtain a composite solid electrolyte coating liquid.

[0061] (2) Preparation of composite solid electrolyte coated diaphragm:

[0062] On a glass plate with a polypropylene base film laid flat, the composite solid electrolyte coating liquid is evenly coated on the polypropylene base film by scraping, and then heated in an oven at 80°C for 48 hours to allow the electrolyte to completely polymerize and solidify, and then washed with water twice to remove the residual NMP solvent, thereby obtaining a composite solid electrolyte coated diaphragm.

[0063] (3) Assembly of button batteries:

[0064] In an argon environment, the composite solid electrolyte coated diaphragm was placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium-ion battery electrolyte was added to assemble a CR2032 button battery.

[0065] Example 7

[0066] (1) Preparation of composite solid electrolyte coating solution:

[0067] First, ethyl methyl carbonate and diethyl carbonate are mixed and stirred in a weight ratio of 1:4 to form a uniform solution, and then 20wt% of lithium fluoride is added to the mixed solution of ethyl methyl carbonate and diethyl carbonate, and then 0.4wt% of cyclohexanone peroxide and 10wt% of Li2S-P2S5-Li4SiO4 inorganic solid electrolyte are added thereto, and finally NMP solution dissolved with 4wt% PVDF is added to obtain a composite solid electrolyte coating liquid.

[0068] (2) Preparation of composite solid electrolyte coated diaphragm:

[0069] On a glass plate with a polypropylene base film laid flat, the composite solid electrolyte coating liquid is evenly coated on the polypropylene base film by scraping, and then heated in an oven at 80°C for 48 hours to allow the electrolyte to completely polymerize and solidify, and then washed with water twice to remove the residual NMP solvent, thereby obtaining a composite solid electrolyte coated diaphragm.

[0070] (3) Assembly of button batteries:

[0071] In an argon environment, the composite solid electrolyte coated diaphragm was placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium-ion battery electrolyte was added to assemble a CR2032 button battery.

[0072] Comparative Example 1

[0073] (1) Preparation of polymer solid electrolyte coating solution:

[0074] First, ethyl methyl carbonate and diethyl carbonate are mixed and stirred in a weight ratio of 1:4 to form a uniform solution, and then 20wt% of lithium bis(difluoromethanesulfonyl)imide is added to the mixed solution of ethyl methyl carbonate and diethyl carbonate, and then 0.3wt% of 2,2'-diazoisobutyronitrile is added thereto, and finally an NMP solution containing 4wt% PVDF is added to obtain a polymer solid electrolyte coating solution.

[0075] (2) Preparation of polymer solid electrolyte coated diaphragm:

[0076] On a glass plate with a polypropylene base film laid flat, the polymer solid electrolyte coating liquid is evenly coated on the polypropylene base film by scraping, and then heated in an oven at 80°C for 48 hours to completely polymerize and solidify the electrolyte, and then washed with water twice to remove the residual NMP solvent, thereby obtaining a polymer solid electrolyte coated diaphragm.

[0077] (3) Assembly of button batteries:

[0078] In an argon environment, the polymer solid electrolyte coated diaphragm was placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium-ion battery electrolyte was added to assemble a CR2032 button battery.

[0079] Comparative Example 2

[0080] (1) Preparation of Inorganic Solid Electrolyte Coating Liquid:

[0081] 8wt% Li 10 GeP2S 12 The inorganic solid electrolyte is finally added with a NMP solution containing 4 wt % PVDF to obtain an inorganic solid electrolyte coating liquid.

[0082] (2) Preparation of inorganic solid electrolyte coated diaphragm:

[0083] On a glass plate with a polypropylene base film laid flat, the inorganic solid electrolyte coating liquid is evenly coated on the polypropylene base film by scraping, and after two water washes, the residual NMP solvent is removed, and then heated in an 80°C oven for 10 minutes to completely solidify the electrolyte, thereby obtaining an inorganic solid electrolyte coated diaphragm.

[0084] (3) Assembly of button batteries:

[0085] In an argon environment, the inorganic solid electrolyte coated diaphragm is placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium-ion battery electrolyte is added to assemble a CR2032 button battery.

[0086] The battery obtained in the above embodiment was subjected to relevant performance tests, and the test results are shown in Table 1 below:

[0087] Table 1 Battery performance test of examples and comparative examples

[0088]

[0089]

[0090] It can be seen from Table 1 that the elastic modulus of the battery obtained by using the composite solid electrolyte coating diaphragm of the present invention is greatly increased, thereby inhibiting the generation of lithium dendrites and greatly improving the battery safety performance. The internal resistance of the battery is reduced, and the ionic conductivity is greatly increased, thereby improving the cycle stability of the battery.

[0091] The above embodiments are only illustrative of the principles and performances of the present invention, as well as some embodiments of its application. A person skilled in the art may make several modifications and improvements without departing from the inventive concept of the present invention, and all of these belong to the protection scope of the present invention.

Claims

1. A method for preparing a composite solid electrolyte coating diaphragm, characterized in that The method is carried out according to the following steps: (1) Preparation of composite solid electrolyte coating liquid: First, ethyl methyl carbonate and diethyl carbonate are mixed and stirred in a weight ratio of 1:4 to form a uniform solution, and then 10-40 wt% of lithium salt is added to the mixed solution of ethyl methyl carbonate and diethyl carbonate, and then 0.2-0.6 wt% of initiator and 3-10 wt% of inorganic solid electrolyte are added thereto, and finally NMP solution containing 4 wt% PVDF is added to obtain a composite solid electrolyte coating solution; wherein the inorganic solid electrolyte is Li 10 GeP2S 12 , Li 1 / 2 La 1 / 2 TiO3, Li2S-P2S5-Li4SiO4, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 or Li 14 ZnGe4O 16 ; The particle size D50 of the inorganic solid electrolyte ranges from 0.4 to 1.5 microns; (2) Preparation of composite solid electrolyte coated diaphragm: The polypropylene base film is laid flat on a glass plate, and the composite solid electrolyte coating liquid obtained in step (1) is evenly coated on the polypropylene base film by scraping, and then heated in an oven at 80°C for 48 hours to allow the electrolyte to completely polymerize and solidify, and then washed with water to remove the residual NMP solvent, thereby obtaining a composite solid electrolyte coated diaphragm.

2. The method for preparing a composite solid electrolyte coating membrane according to claim 1, characterized in that The lithium salt described in step (1) is lithium bis(difluoromethanesulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium difluorooxalatoborate, lithium fluoride, lithium perchlorate or lithium tetrafluoroborate.

3. The method for preparing a composite solid electrolyte coating membrane according to claim 1, characterized in that The initiator described in step (1) is 2,2'-diazoisobutyronitrile, azobisisoheptanenitrile, diisopropylbenzene peroxide, cyclohexanone peroxide or dimethyl azobisisobutyrate.

4. A composite solid electrolyte coating membrane obtained by the preparation method according to any one of claims 1 to 3, characterized in that The diaphragm is used in CR2032 button battery. The specific application conditions are: in an argon environment, the composite solid electrolyte is coated The diaphragm is placed between the lithium iron phosphate positive electrode and the lithium metal negative electrode, and then 1 / 4 of the liquid lithium-ion battery electrolyte is added to assemble CR2032 button cell battery.

Citation Information

Patent Citations

  • Composite quasi-solid-state electrolyte and preparation method thereof, and lithium battery or lithium ion battery containing composite quasi-solid-state electrolyte

    CN107645013A

  • Composite electrolytes

    CN107710455A

  • A solid-state electrolyte membrane, a secondary battery comprising a solid-state electrolyte membrane, and a method for manufacturing a solid-state electrolyte membrane

    US20220131231A1